Green human resource management and green behavior: Mediating work engagement - Kania, Dewi (International Journal of Applied Finance and Business Studies, 2024)
Today’s eco-friendly practices have become a particular concern in the business environment. This study aimed to test and analyze how GHRM can affect green behavior mediated by work engagement. This study used quantitative research methods with a PLS-SEM-based causality approach. The sample in this study was 82 respondents at PT. Nikomas is resplendent. The results of this study partially show that GHRM had a significant influence on green behavior; GHRM has a positive and significant effect on work engagement; work engagement produces a positive and significant influence on green behavior, while work engagement can mediate positively and significantly in influencing GHRM on green behavior.